PENGARUH PARTISIPASI ANGGARAN, ENVIRONMENTAL UNCERTAINTY, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA MANAJERIAL (Studi Kasus Pada PT Bank CIMB Niaga Tbk) - Ayu, Winda Permata; Widiyati, Dian (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This study aims to determine the effect of budget participation, environmental uncertainty, and leadership style on managerial performance at PT Bank CIMB Niaga Panglima Polim in 2024. The sampling technique used purposive sampling and obtained a sample of 39 respondents. This research method uses associative quantitative. This research uses descriptive statistical analysis, data quality tests, classical assumption tests, and hypothesis tests consisting of multiple linear regression analysis tests, coefficient of determination (R2), F tests, and t tests processed using SPSS version 25. The results of this research show that budget participation, environmental uncertainty, and leadership style simultaneously influence managerial performance. Partially, budget participation has no effect on managerial performance, while environmental uncertainty and leadership style influence managerial performance.